O analitismo verbal e a expressão do futuro no português brasileiro: um estudo diacrônico - Alcione Gonçalves (2013)
This study carries out a diachronic investigation of the expansion of verbal periphrasis as future markers, taking into consideration the grammaticalization processes that underlie them, by focusing on the modal and time expressions. Firstly, we analyze the grammaticalizationprocess of the verb ir in its lexical and grammatical forms (ir + infinitive). Afterwards, we look at its gradual expansion as a future marker, in comparison with the uses of its synthetic form (-rei). The third stage of the analysis was based on the investigation of the grammaticalization processes of the modal verbs poder and dever, in their most abstractconceptions, as they were followed by a verb in the infinitive (Modal + infinitive) in order to express possibility/probability. Lastly, we investigate the ir + estar + gerund construction, which is being consolidated as another alternative for future expression in the Portugueselanguage. The research is grounded on Hopper & Traugott´s (1993) and Heine et al..´s (1991) grammaticalization theories, as well as on the methodology developed by Vianna (2000) and Vitral (2006), and aims to understand the synthetic, morphophonemic and semantic rules ofverbal constructions forming the future tense in the modern and contemporary Brazilian Portuguese language. The methodological proposal entails the calculations of frequency that work as a mechanism to compare how certain elements behave in their lexical andgrammatical functions, providing us with a quantitative rate of the grammaticalization processes. Our objective is then to determine at which stage verbal periphrasis became more frequent, by resuming the issue of instability in the formation of the future tense, whileunderstanding that language is a self-regulating mechanism, and that the future forms are inserted in a cyclic, continuous process of shifts between synthetic and analytic forms. This research enabled us to observe, quantitatively, the grammaticalization process of theperiphrasis ir + infinitive indicating the future tense. It also allowed us to identify that other periphrases (modal + infinitive and ir + estar+ gerund) have been taking more and more space in the language to indicate futurity, although we must consider that the simple future tense (-rei) is still frequently used in writing, especially in genres that require more monitoring.